FORMATION OF A FLOCK OF MOTHER FISH AND REPRODUCTION OF FISH - Allamuratova Bibizada Kadirbay kizi (European Journal of Interdisciplinary Research and Development, 2023)
This article explores the formation of mother fish flocks and their impact on fish reproduction through a combination of observational studies and data analysis. It highlights the ecological significance of this social behavior and the benefits it provides to fish populations.